1993
DOI: 10.1002/ffj.2730080403
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of essential oils of new Citrus hybrids

Abstract: The chemical composition of the essential oils of seven new citrus hybrids, obtained by crossbreeding grapefruit with clementine, was analysed by GC-MS. A total of 58 components were detected, 48 of them fully characterized. Limonene is consistently the main component of all the essential oils of the hybrids and the parents. Hybrid-hybrid and parent-hybrid differences in oil composition are reported. Variations during the fruit development of the percentage of six classes (non-oxygenated monoterpenes, oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As previously observed (Dugo et al, 1990;Moshonas et al, 1991;Ruberto et al, 1993Ruberto et al, , 1994Scora et al, 1970;Soost, 1987;Soost andCameron, 1980, 1985), the chemical composition of the essential oils of hybrids appears as the superimposition of those of the parent species, the composition of an individual hybrid beingcloser to one or the other parent. Limonene is the main component, representing about 95% of the total oils of both hybrids and parents.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As previously observed (Dugo et al, 1990;Moshonas et al, 1991;Ruberto et al, 1993Ruberto et al, , 1994Scora et al, 1970;Soost, 1987;Soost andCameron, 1980, 1985), the chemical composition of the essential oils of hybrids appears as the superimposition of those of the parent species, the composition of an individual hybrid beingcloser to one or the other parent. Limonene is the main component, representing about 95% of the total oils of both hybrids and parents.…”
Section: Resultsmentioning
confidence: 68%
“…In the course of our continued phytochemical studies of new Citrus hybrids, we have reported the chemical composition of the essential oils of new Citrus fruits (Ruberto et al, 1993(Ruberto et al, , 1994. The present investigation deals with the chemical analysis of the oils of two new hybrids obtained by a cross between clementine (Citrus clementina Hort.…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, the "Istituto Sperimentale per I'Agtumicoltura," in Acireale (Sicily), started a research program aimed at the new citrus crossbreeding and at the study of their fruit chemistry (1)(2)(3)(4) Compounds didn't mention between that identified in clementine oil (10) of this study a new citnis hybrid was obtained by crossbreeding the diploid clementine (Citrus clementina Hort ex Tan.) and the tetraploid lemon [Citms limon (L.) Burm f.1.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, our interest, in these last years, has been focused on the study of the chemical composition of new Citrus hybrids (Rapisarda et al, 1990(Rapisarda et al, , 1995Ruberto et al, 1993Ruberto et al, , 1994Ruberto et al, , 1997 with the aim of phytochemical characterization and, possibly, the evaluation of these new fruits for their introduction into the fresh market and into the industrial chain of trasformation.…”
mentioning
confidence: 99%
“…With this in mind, the joint research of our groups concerns the genetic improvements of high quality cultivars and the production of new citrus fruits, namely hybrids (Starrantino, 1980(Starrantino, , 1992. In particular, our interest, in these last years, has been focused on the study of the chemical composition of new Citrus hybrids (Rapisarda et al, 1990(Rapisarda et al, , 1995Ruberto et al, 1993Ruberto et al, , 1994Ruberto et al, , 1997 with the aim of phytochemical characterization and, possibly, the evaluation of these new fruits for their introduction into the fresh market and into the industrial chain of trasformation.…”
mentioning
confidence: 99%